POLITICAL REGIMES AND ECONOMIC PERFORMANCE - JIHAN SHANABLI (Challenges of the Knowledge Society, 2012)
The present paper brings a contribution to the research area dedicated to the relationship between political regimes and economic growth. Implicitly the interdependence relation between the two large domains, namely politics and economy will be the core of the study. The major focus will be on the way politics influences the economic evolution and development of a country. The premise is that political institutionsplay an essential part with respect to the economic performance as they have the potential to relax the constraints imposed over the economic structure and not only. The three basic dimensions used in constructing the paper are thedegree of political freedom, the level of political stability and the level of political security.